Nutrition and lifestyle in relation to bowel movement frequency: a cross-sectional study of 20630 men and women in EPIC-Oxford - Sanjoaquin, M; Appleby, P; Spencer, E; Key, T (Cambridge University Press, 2004)
Objective: To investigate the relationships between nutritional and lifestyle factors and bowel movement frequency. Design: Cross-sectional analysis using data from a prospective study. Mean numbers of bowel movements were calculated in relation to a range of factors. In addition, individuals were categorised according to frequency of bowel movements: fewer than 7 per week (‘less than daily’) versus 7 or more per week (‘daily’), and odds ratios were calculated from logistic regression models. Results for each factor were adjusted for the other factors under consideration. Setting: The European Prospective Investigation into Cancer and Nutrition, Oxford cohort (EPIC–Oxford), UK. Participants: In total, 20 630 men and women aged 22–97 years at recruitment. Thirty per cent of the subjects were vegetarians or vegans. Results: Women had fewer bowel movements on average than men, and were less likely to have daily bowel movements. Mean bowel movement frequency was higher in vegetarians (10.5 in men, 9.1 in women) and especially in vegans (11.6 in men, 10.5 in women) compared with participants who ate meat (9.5 in men, 8.2 in women). There were also significant positive associations between bowel movement frequency and body mass index (BMI), intakes of dietary fibre and non-alcoholic fluids, for both men and women. Vigorous exercise was positively associated with bowel movement frequency in women although results for men were less clear. Alcohol intake was positively associated with bowel movement frequency in men but not in women. Conclusion: Being vegetarian and especially vegan is strongly associated with a higher frequency of bowel movements. Moreover, having a high intake of dietary fibre and fluids and a high BMI are associated with an increase in frequency of bowel movements.